Bangladesh : Finding It Difficult to Keep Cool - Mahmud, Iffat (World Bank, Washington, DC, 2021)
Bangladesh is a low-lying river delta with a long coastline of 711 kilometers and floodplains that occupy 80 percent of the country (Hasib and Chathoth 2016). The country experiences a multitude of natural disasters every year. Severe floods, cyclones, storms, tidal surges, and river erosion frequently cause loss of life, with devastating social and economic impacts. These extreme weather events are expected to be exacerbated by the effects of climate change (Rahman et al. 2019). The Government of Bangladesh’s National Climate Vulnerability Assessment identified a number of climate-related hazards in 2018 that are critical for Bangladesh, including increasing temperature and heat stress; more frequent and longer droughts; increasing rainfall intensity; higher river flows and flood risks; greater riverbank erosion; sea level rises and salinity intrusion; landslides; and increasing intensity of cyclones, storm surges, and coastal flooding (Government of Bangladesh 2018). In rural areas, where nearly 80 percent of the population live, climate change has an immediate and direct effect on the health and wellbeing of millions of people who depend on natural resources for their livelihoods. The impacts of climate change are also increasingly felt in large cities that are exposed to various climate-induced hazards, including variations in temperature, excessive and erratic rainfall, water logging, flooding, and heat and cold waves (Rabbani et al. 2011). These hazards are exacerbated by high population density, poverty, rural–urban migration, illiteracy, and a lack of public utilities and services (Rabbani et al. 2011). Rapid urbanization and a growing urban slum population are quickly changing the population dynamics in Bangladesh, and this has implications for climate-induced health risks (Mani and Wang 2014). The country has the world’s highest rate of mortalities that are caused by natural disasters, with more than half a million people lost to disaster events since 1970. Most of these deaths have occurred during floods or cyclones (Nahar 2014). Not long ago, Bangladesh was hit by two major cyclones: Sidr in 2007 and Aila in 2009. Cyclone Sidr killed 3,406 people while more than 55,000 sustained physical injuries. Heavy rain and tidal waves caused by wind effects led to extensive physical destruction and damage to crops and livestock. After Cyclone Sidr, an assessment by the Government of Bangladesh found widespread outbreaks of diarrhea, dysentery, acute respiratory infection, and pneumonia. Children ages five or younger were the most vulnerable (Kabir et al. 2016b). Cyclone Aila hit the southern coastline of Bangladesh and partly damaged the Sundarbans. Along with outbreaks of diarrheal diseases was an acute scarcity of drinking water and food (Kabir et al. 2016b). With the number and intensity of such storms or cyclones projected to increase, climate change can reverse some of the significant gains Bangladesh has made in improving health-related outcomes, particularly in reducing child mortality, improving maternal health, and improving nutritional outcomes.